Investigating the impact of acceptance and commitment therapy for mental healthcare professionals: the effect on patients´ self-stigmatization, a pilot study - Helmus, Kim L.; van Doorn, Marilon; de Koning, Mariken B.; Myin-Germeys, Inez; Schirmbeck, Frederike N.; van Amelsvoort, Therese A. M. J.; Nieman, Dorien H.; Jaspers, Monique W. M.; Popma, Arne; de Haan, Lieuwe (Frontiers in Psychiatry, 2025)
BackgroundA significant proportion of mental health care professionals (MHCPs) hold stigmatizing attitudes about their patients. When patients perceive and internalize these beliefs, self-stigmatization can increase. Acceptance and Commitment Therapy (ACT) may decrease stigmatizing attitudes by changing the ‘us’ versus ‘them’ thinking into continuum beliefs. In the present study MHCPs were given an ACT-based training, aiming to decrease stigmatization, hypothesizing that self-stigmatization of their patients will subsequently decrease.MethodsAn RCT with a 2 (pre-test/post-test) x 2 (no training/training) design was conducted. A total of 41 MHCPs participated, 20 were randomized to the experimental and 21 to the control condition respectively. The MHCPs in the experimental condition received an ACT-based training, MHCPs in the control condition received no training. From every MHCP, one of their patients participated in the pre- and post-measurement. As the primary outcome, patients’ awareness, agreement, application and hurt-self, was measured using the Self Stigma of Mental Illness Scale - Short Form (SSMIS-SF), before and after the MHCPs’ ACT-based training.ResultsSignificant group x time interaction effects were found for ‘application’ (internalization of mental illness stereotypes) in patients after the ACT-based training of their MHCP: F (1,39) = 9.33, p < 0.01, ηp2 = .85. On the contrary, no effect was found on the subscales ‘awareness’, ‘agreement’ and ‘hurt-self’.ConclusionPreliminary results suggest that a brief ACT training for MHCP might heighten their awareness and contribute to reduction of their stigmatizing attitudes and behavior, leading to less application of self-stigmatizing beliefs in their patients.